2019
DOI: 10.3390/antiox9010006
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Antioxidants in Coffee Leaves: Impact of Botanical Origin and Maturity on Chlorogenic Acids and Xanthones

Abstract: Natural polyphenols are important dietary antioxidants that significantly benefit human health. Coffee and tea have been shown to largely contribute to the dietary intake of these antioxidants in several populations. More recently, the use of coffee leaves to produce tea has become a potential commercial target, therefore prompting studies on the quantification of polyphenols in coffee leaves. In this study a variety of coffee leaf species, at different development stages, were analyzed using ultra-high pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
31
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 43 publications
(107 reference statements)
8
31
1
2
Order By: Relevance
“…Therefore, it is essential that the human diet contains, among other nutrients, phenolic compounds [ 13 ]. Coffee is one of the dietary sources of these compounds [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is essential that the human diet contains, among other nutrients, phenolic compounds [ 13 ]. Coffee is one of the dietary sources of these compounds [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The amount of the acid decreases as coffee beans mature. It has been demonstrated that CLA has a positive effect on glucose and lipid metabolism, and thus, reduces the risk of diabetes, obesity, cardiovascular and liver diseases and cancer [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, these results can be related to the constitutive characteristics of this alkaloid in the evaluated genotypes. Other studies quantified trigonelline in coffee leaves (Ashihara and Watanabe, 2014, Silva et al., 2019, Monteiro et al., 2020), but without relating to disease resistance. Trigonelline acts as a chemical defence that protects tissues from herbivorous predators such as insect larvae in Murraya paniculata (Ashihara and Watanabe, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Xanthone content in young coffee leaves is as high as in mango leaves. The content of 5-CQA, 3,5-DiCQAm, and mangiferin in coffee leaves proves that kawa daun beverage has antioxidant activities and strong anti-inflammatory activities [25].…”
Section: Introductionmentioning
confidence: 94%